Localization-triggered bacterial pathogenesis. (October 2015) - Lood, Rolf; Waldetoft, Kristofer Wollein; Nordenfelt, Pontus
Bacterial infections are becoming an increasing problem worldwide and there is a need for a deeper understanding of how bacteria turn pathogenic. Here, we suggest that one answer may be found by taking into account the localization of the bacteria, both at an anatomical level and at a microenvironment level. Both commensals and traditional pathogens alter their interaction with the human host depending on the local surroundings – turning either more or less virulent. These localization effects could derive from the characteristics of different anatomical sites but also from local differences within a microenvironment. In order to understand the adaptive functions of bacterial virulence factors, we need to study the bacteria in the environments where they have evolved.